Improved electrochemical and air stability performance of SeS2 doped argyrodite lithium superionic conductors for all-solid-state lithium batteries. (20th February 2023) - Kim, Hak-Min; Subramanian, Yuvaraj; Ryu, Kwang-Sun
Abstract: At present, sulfide-based solid electrolytes have attracted considerable attention, especially argyrodite-type solid electrolyte, Li6 PS5 X (X = Cl, Br, I), due to its appropriate mechanical strength and high ionic conductivity (>10 –3 S/cm). However, it still falls short of liquid electrolytes in terms of ionic conductivity and has the fatal drawback of being unstable to moist air. In this report, we prepare SeS2 doped Li6 PS5 Cl through high-energy ball milling followed by heat treatment. We also confirm the structural properties using powder X-ray diffraction (XRD) and Raman analyses. Next, we perform surface morphology and elemental analysis using a field emission scanning electron microscope (FE-SEM) and energy-dispersive X-ray spectroscope (EDS). The synthesized Li6.03 P0.97 Se0.03 S5 Cl electrolyte shows a higher ionic conductivity of 5.4 mS/cm and a lower activation energy of 0.287 eV compared to pristine Li6 PS5 Cl (4.4 mS/cm, 0.292 eV) at 25 ℃, and it also shows good stability against Li metal. The optimized electrolyte shows a higher initial discharge capacity of 175 mAh/g and coulombic efficiency of 67.6%. Interestingly, Li6.03 P0.97 Se0.03 S5 Cl showed 61.5% of the 1 C rate capacity compared to that at the 0.05 C rate, which was significantly improved compared to the corresponding value of the pristine. Finally, to measure the air stability properties, the H2 S generation amount test and EIS test were both performed before and after exposure to air and Li6.03 P0.97 Se0.03 S5 Cl shows a high ionic conductivity of 3.06 mS/cm after 30 min dry air exposure.